2021
DOI: 10.2147/ijgm.s316670
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Angiogenic Biomarkers in Pregnancy Associated with Gestational Diabetes

Abstract: Background: Gestational diabetes mellitus (GDM) typically occurs during the third trimester of pregnancy. Maternal hyperglycemic may influence the expression of pro-and antiangiogenic factors. Altered levels of angiogenic biomarkers in GDM pregnant women are associated with abnormal placentation. This study aimed to investigate the rates of expression of five angiogenic biomarkers called vascular endothelial growth factor-A (VEGF-A), angiopoietin-2, endoglin, endothelin-1, and granulocyte colony-stimulating fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Multiple blood vessels of the mother pass through the paracrine, while autocrine regulatory substances and environmental effects affect the activity of the placenta [ 27 ], which then affects fetus. Vascular function is clearly abnormal in the context of inflammation and oxidative stress caused by a blood lipid hormone disorder [ 28 , 29 ] and various vascular factors affect the normal growth of blood vessels.…”
Section: Gdm and Vegfmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple blood vessels of the mother pass through the paracrine, while autocrine regulatory substances and environmental effects affect the activity of the placenta [ 27 ], which then affects fetus. Vascular function is clearly abnormal in the context of inflammation and oxidative stress caused by a blood lipid hormone disorder [ 28 , 29 ] and various vascular factors affect the normal growth of blood vessels.…”
Section: Gdm and Vegfmentioning
confidence: 99%
“…Data from recent years imply that VEGF is strongly associated with GDM. In some GDM patients with VEGF-A, endothelin and endothelin-1 levels were significantly increased [ 27 ]. VEGF-A, endothelin, and G-CSF (granulocyte colony-stimulating factor) have been shown to have a significant positive correlation with endothelin-1.…”
Section: Gdm and Vegfmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous studies found that insulin resistance is a major contributor to the development of GDM. 30–32 These findings suggest that ATG7 may mediate insulin resistance in the pathogenesis of GDM.…”
Section: Discussionmentioning
confidence: 92%
“…Only two studies reported that there is no significant difference in ET-1-mediated placental perfusion and vasoconstriction between normal pregnancy and PIH placenta (Inayatulla et al, 1993;Read et al, 1999). Serum ET-1 level in GDM was significantly higher compared to controls (Al-Ofi et al, 2021), while both Swiderski and Beata Telejko, et al showed that plasma ET-1 levels in women with GDM were not significantly different from those observed in pregnant women without GDM (Telejko et al, 2009;Swiderski et al, 2010). Although no relevant studies have been found to prove abnormal plasma ET-1 levels in pregnant women with GDM, some studies have shown that women with GDM are less sensitive to ET-1 than pregnant women without GDM (Ang et al, 2001).…”
Section: Endothelin-1mentioning
confidence: 94%